Cold Crack Susceptibility studies on High Strength Low Alloy Steel 950A using Tekken Test - Velumani, Manivelmuralidaran; sakthivel, M.; Balaji, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In This research article deals with the study of cold cracking susceptibility of High Strength Low Alloy Steel (HSLA) 950A using Gas Metal Arc Welding process (GMAW). The cold cracking is a general problem while welding HSLA steels. It thus becomes mandatory to have a novel method of welding to minimize the effects of cold cracking. The cold cracking tendency of the material is determined using the Y groove Tekken test and the test is carried out with DIN EN ISO 17642â€“2 standard. The welding of the base metal has been carried out using the low hydrogen electrode ER 70SD2. The test procedure is followed under self-restraint condition for determining cold cracking susceptibility of weld metal. Micro structural constituent of the weld metal plays an important role in determining the cold crack susceptibility of the weld metal. Hence an attempt has been made to impart the microstructure having high resistance to cold cracking.Â It has been observed that Acicular ferrite microstructure in the weld metal increases the cold cracking resistance of the welded joint.Â In the present study, the effect of preheating temperature on cold crack susceptibility analyzed by varying the preheating temperature 100ÂºC, 150ÂºC and acicular ferrite microstructure observed in the microstructure analysis of the welded specimen. The effect of microstructure on cold cracking has also been established. But due to very limited range of temperature, the effect of preheating temperature on cold crack susceptibility was inconclusive. But the formation of acicular ferrite microstructure will have greater influence on cold crack susceptibility. In future, effects of Nickel, Manganese and other alloying elements of the filler material in increasing cold cracking resistance can also be studied for far reaching prospects of the research.